Cytocompatibility of a matrix of methylated cassava starch and chitosan. (November 2013) - Sívoli, L; Pérez, E; Caraballo, D; Rodríguez, JP; Rodríguez, D; Moret, J; Sojo, F; Arvelo, F; Tapia, M; Colina, M; Alvarez-Barreto, JF
Starches can be used to form edible or biodegradable films, and recently modified starches have been used to form self-supporting films by casting from aqueous solution. In this work, we aimed to propose a novel starch-based composite biomaterial matrix for use in biomedical applications, especially tissue engineering. The goal of the study was to evaluate the cytocompatibility of composite hydrogels of methylated starch and chitosan, using glutaraldehyde as the cross-linker. Commercial cassava starch with high purity (96.69%) was methylated with dimethyl sulfate in order to obtain a rigid material that could possibly render stronger mechanical properties to chitosan hydrogels. Therefore, methylated starch was mixed with a solution of chitosan and the cross-linking was induced by the addition of glutaraldehyde, allowing the formation of hydrogel films which were visualized under scanning electron microscopy. The method of fabrication was optimized based on the capacity of the cells to attach to the material and proliferate. After thorough washes with ethanol and saline solution, human fibroblasts were seeded on top of the gels and allowed to grow for 3 to 5 days. Cell viability was measured using an (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) MMT assay, and cell morphology was visualized by light microscopy. It was found that cells were viable at every time point, with their metabolic activity comparable to the controls (tissue culture plastic and chitosan alone), as well as clear cell–matrix interactions. Moreover, an increase in the metabolic activity over time indicated the capacity of the material to support cell proliferation. The proposed methylated starch–chitosan system is an excellent matrix that allows cell adhesion and could thereby be further assessed as a scaffold for tissue engineering.